RELATIONSHIP BETWEEN EXAM ANXIETY AND CHEATING BEHAVIOR: A QUANTITATIVE STUDY OF UNDERGRADUATES IN ENUGU STATE, NIGERIA - Nnaji, Tochukwu C. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Cheating behavior is a critical educational concern across all academic levels globally. The trend is pervasive among higher education students and undermines human and national developments. This study examined cheating behavior among students in tertiary institutions in Enugu State, Nigeria, based on their subjective exam anxiety. Two hundred and thirty-seven undergraduates participated in the study. The students were conveniently pooled from different institutions of higher learning between February and April 2022. They completed self-report measures of the Cognitive Exam Anxiety Scale and the Cheating behavior Scale. The data were analyzed using a Pearson-moment correlation. The finding revealed a statistically significant, moderate positive correlation between exam anxiety and cheating behavior, r (235) = .44, p < .001. Importantly, exam anxiety explained 12.6% of the variation in cheating behavior. The finding has implications for educational and institutional development.